Aspects of the ecology and biology of the isopod, Exosphaeroma hylocoetes, (Barnard, 1940) in three temporarily open/closed southern African estuaries - Henninger, Tony Oskar (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2009)
Temporarily open/closed estuaries (TOCE's) are the numerically dominant type of estuary accounting for â‰ˆ 70 % of all estuaries along the South African coastline. Despite their numerical dominance, aspects of the biology of organisms within these systems, particularly macrocrustacea remain poorly understood. This study firstly assessed the abundance and biomass of the most common isopod, Exosphaeroma hylocoetes, in three Eastern Cape TOCE's, (the West Kleinemonde, East Kleinemonde and Kasouga Estuaries), and their response to mouth breaching events. This study was followed by aspects of the biology of the isopod including their utilisation of submerged macrophytes as a refuge from predation and/or possible food source, as well as the growth rates of the isopods in the laboratory under different environmental conditions. Mean isopod abundances and biomasses ranged between 0 and 4 791 ind. mâ »Â² and 0 and 9.65 mg dwt. mâ »Â² in the West Kleinemonde Estuary and between 0 and 108 ind. mâ »Â² and 0 and 0.318 mg dwt. mâ »Â² in the nearby East Kleinemonde Estuary. In the Kasouga Estuary, the values ranged between 0 and 3 650 ind. mâ »Â² and 0 and 5.105 mg dwt. mâ »Â². Temporal and spatial changes in the abundance and biomass of E. hylocoetes within the three systems was primarily linked to mouth phase, with populations declining when the mouth was open and to a lesser extent, seasonality. In all three estuaries maximum isopod abundances and biomasses were recorded in their middle and upper reaches, which could be ascribed to the presence of submerged macrophytes particularly Ruppia maritima, in two of the estuaries. Males (5.71 Â± 0.41 mm) were significantly larger than females (3.99 Â± 0.26 mm), but the sex ratios were skewed in favour of females, (a common feature in many isopod populations). Females were found carrying brood throughout the study, releasing offspring directly into the water column, to allow recruitment to the populations. The larger the female, the larger the brood carried (up to a maximum of 72 embryo/mancas). Results of laboratory experiments indicate that the close association of Exosphaeroma hylocoetes with submerged macrophytes is a result of the plant stands providing a refuge against predation by selected ichthyofauna. However stable carbon isotope and fatty acid analyses indicate that E. hylocoetes made use of ephiphytic algae and detritus on the stems of R. maritima, rather than the submerged macrophyte itself. There were no significant differences in the growth rates of male and female isopods at combinations of temperature (15 and 25 Â°C) and salinity (15 and 35 "°). Laboratory growth studies revealed that males lived longer than females (25.77 Â± 3.40 weeks vs 21.52 Â± 3.00 weeks), and therefore achieved larger overall size. Females, however, reached sexual maturity (at 2.5 mm) at a faster rate (two to four weeks) than males (5.5 mm after 6.5 to 11 weeks), dependent on temperature. Exosphaeroma hylocoetes with its association with submerged macrophytes, early maturity, its growth rates and longevity, female-biased sex ratios and year-round breeding, all contribute to its success in temporary open/closed estuaries.
Keywords: Estuaries -- South Africa -- Eastern Cape; Estuarine ecology -- South Africa -- Eastern Cape; Isopoda -- South Africa -- Eastern Cape; Estuarine biology -- South Africa -- Eastern; Cape Ruppia maritima